2020
DOI: 10.3390/ijms21041267
|View full text |Cite
|
Sign up to set email alerts
|

CELSR1 Promotes Neuroprotection in Cerebral Ischemic Injury Mainly through the Wnt/PKC Signaling Pathway

Abstract: Cadherin epidermal growth factor (EGF) laminin G (LAG) seven-pass G-type receptor 1 (CELSR1) is a member of a special subgroup of adhesion G protein-coupled receptors. Although Celsr1 has been reported to be a sensitive gene for stroke, the effect of CELSR1 in ischemic stroke is still not known. Here, we investigated the effect of CELSR1 on neuroprotection, neurogenesis and angiogenesis in middle cerebral artery occlusion (MCAO) rats. The mRNA expression of Celsr1 was upregulated in the subventricular zone (SV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…Moreover, there is growing evidence in the brain that factors such as CELSR1 (Cadherin epidermal growth factor (EGF) laminin G (LAG) seven-pass G-type receptor) are responsible for neuroprotective effects on cerebral ischemia injury [19]. This is consistent with the recent investigations of Schuhmann, M.K.…”
supporting
confidence: 81%
“…Moreover, there is growing evidence in the brain that factors such as CELSR1 (Cadherin epidermal growth factor (EGF) laminin G (LAG) seven-pass G-type receptor) are responsible for neuroprotective effects on cerebral ischemia injury [19]. This is consistent with the recent investigations of Schuhmann, M.K.…”
supporting
confidence: 81%
“…The inhibition of PKC or Akt that accompanies neuronal death has been observed in the brain under excitotoxic conditions, and this excitotoxic brain damage also appears to be prevented by PKC or Akt activation. 47,48 In addition, PKC has been found to phosphorylate the C-terminal intracellular regulatory domain of the AMPA receptor subunit, including GluR2, 49 and this PKC-GluR2 axis is known to play a neuroprotective role in glutamate-induced neurotoxicity. 50 In our study, we found that the KA-induced decreases in the phosphorylation of the AMPA receptor subunit GluR2 and PKCα were significantly increased by eupafolin, implying that the PKC-GluR2 axis is also involved in the anticonvulsant and neuroprotective effects of eupafolin.…”
Section: ■ Discussionmentioning
confidence: 99%
“…So, the future research of stroke must expand its horizon to find new strategies. Neurogenesis is a promising step toward the recovery and restoration of brain function after stroke and other neurogenerative diseases [39][40][41] . Our study demonstrated that in an early stage of ischemic stroke, IL-17, as an important indicator of poor prognosis, was involved in the proliferation relevant signal pathway-PI3K/Akt pathway, and responsible for suppressing local NSCs stemness and neurogenesis, as well as infraction area.…”
Section: Discussionmentioning
confidence: 99%